Perilaku Masyarakat Dalam Penanganan Sampah di Pasar Natar Kabupaten Lampung Selatan - Fernando, Riky (BUGUH: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
The market is one of the places with high waste generation. This study aims to determine the behavior of the community in handling waste in Natar Market, South Lampung Regency. This research was carried out with a qualitative approach. The informants used in this study were 15 people who were selected proportionally consisting of sub-district officials, the community, and the janitor. The focus of this research is the behavior of the community as seen from the knowledge and attitudes of the community in dealing with the generated waste. The results of the study indicate that public knowledge is still low because there is still a lack of public understanding of the activities of selecting and collecting waste safely for health and the environment, meaning that it does not interfere with health and the environment, while the attitude shown through the community's response is still not good for waste handling activities because the community has not performed their obligations to sort waste between wet waste and dry waste and place it in different containers. Keywords: Behavior, Community, Handling of Waste.